Learning and reflections from the iHV Emotional Wellbeing at Work Champions Programme. (2nd October 2022) - Baldwin, Sharin; Stephen, Rachel; Kelly, Patricia; Bishop, Philippa
Abstract : The health visiting workforce, along with healthcare staff from other sectors, have reported increased rates of stress, anxiety and burnout following the COVID-19 pandemic. In response, the Institute of Health Visiting developed an Emotional Wellbeing at Work (EWW) programme in 2020. Following the successful implementation and evaluation of the original programme, a Champions cascade delivery model was adopted to increase the reach of the programme and build greater capacity to enhance the emotional wellbeing of the health visiting workforce. This article discusses the evaluation, learning and reflections from the EWW programme, developed specifically for the health visiting workforce in the UK.